Black Lives Matter in TESOL: De‐Silencing Race in a Second Language Academic Literacy Course. Issue 1 (30th November 2016) - Guerrettaz, Anne Marie; Zahler, Tara
Abstract : As racial tensions and reports of violence have become prominent in news and social media, U.S. society has been responding, struggling, and changing. This complex political and social situation can be particularly confusing for international students studying at U.S. universities. English language teachers are especially well positioned to create space for exploring this complexity and supporting learners' understanding of these events in light of their historical context. This report on the authors' collaborative reflective practice examines a second language academic literacy course through the lens of multiliteracies (New London Group, 1996 ). This approach acknowledges the multilingual, multicultural landscape of the United States and draws on multiple modalities and discourses in literacy education (Cope & Kalantzis, 2009 ). The core course novel that is the focus of the current article, A Lesson Before Dying (Gaines, 1993 ), is the story of a young African American man during the Jim Crow era who is sentenced to death for a crime he did not commit. These teachers noticed that students struggled to put race‐related issues that are central to the text into meaningful historical and social context. The authors responded by situating the novel through inclusion of key supplementary materials on themes such as African American Vernacular English and Black masculinities. The pedagogy challenged racist master narratives that permeate American society, as reflected in both the course novel and current events, and constructed counternarratives. The resources described here are immediately relevant to English language classrooms in the United States at this important historical moment.